Annexin A2 as a target endothelial cell membrane autoantigen in Behçet's disease - Chen, Peng (Sci Rep, 2015)
Cell membrane proteins are believed to play a critical role in the pathogenesis of autoimmune diseases. However, few membrane autoantigens have been linked with Behçet's disease. Here, a cell-chip was performed to identify autoantibody target cells, and the suspected autoantigens were detected using immunoblotting. The amino acid sequences of the detected proteins were determined using LC-MALDI-TOF/TOF. Putative proteins were recombinantly expressed and purified, and a corresponding ELISA was developed and clinically validated using real clinical samples. It was found that a 36-kDa membrane protein - annexin A2 - was detected in approximately one-third of the patients' blood circulation. The immunohistochemistry results showed that annexin A2 was highly expressed in vascular endothelial cells. Moreover, vascular involvement was significantly higher in the anti-annexin A2 antibody-positive group versus the anti-annexin A2 antibody-negative group among all the clinical samples analyzed, indicating that annexin A2 is a novel endothelial cell membrane antigen involved in Behçet's disease.